Tumour-specific delivery of siRNA-coupled superparamagnetic iron oxide nanoparticles, targeted against PLK1, stops progression of pancreatic cancer. Issue 11 (12th May 2016) - Mahajan, Ujjwal M; Teller, Steffen; Sendler, Matthias; Palankar, Raghavendra; van den Brandt, Cindy; Schwaiger, Theresa; Kühn, Jens-Peter; Ribback, Silvia; Glöckl, Gunnar; Evert, Matthias; Weitschies, Werner; Hosten, Norbert; et al.
Abstract : Objective: Pancreatic ductal adenocarcinoma (PDAC) is one of the most aggressive malignancies and is projected to be the second leading cause of cancer-related death by 2030. Despite extensive knowledge and insights into biological properties and genetic aberrations of PDAC, therapeutic options remain temporary and ineffective. One plausible explanation for the futile response to therapy is an insufficient and non-specific delivery of anticancer drugs to the tumour site. Design: Superparamagnetic iron oxide nanoparticles (SPIONs) coupled with siRNA directed against the cell cycle-specific serine-threonine-kinase, Polo-like kinase-1 (siPLK1-StAv-SPIONs), could serve a dual purpose for delivery of siPLK1 to the tumour and for non-invasive assessment of efficiency of delivery in vivo by imaging the tumour response. siPLK1-StAv-SPIONs were designed and synthesised as theranostics to function via a membrane translocation peptide with added advantage of driving endosomal escape for mediating transportation to the cytoplasm (myristoylated polyarginine peptides) as well as a tumour-selective peptide (EPPT1) to increase intracellular delivery and tumour specificity, respectively. Results: A syngeneic orthotopic as well as an endogenous cancer model was treated biweekly with siPLK1-StAv-SPIONs and tumour growth was monitored by small animal MRI. In vitro and in vivo experiments using a syngeneic orthotopic PDAC model as well as the endogenous LSL-Kras G12D, LSL-Trp53 R172H, Pdx-1-Cre model revealed significant accumulation of siPLK1-StAv-SPIONs in PDAC, resulting in efficient PLK1 silencing. Tumour-specific silencing of PLK1 halted tumour growth, marked by a decrease in tumour cell proliferation and an increase in apoptosis. Conclusions: Our data suggest siPLK1-StAv-SPIONs with dual specificity residues for tumour targeting and membrane translocation to represent an exciting opportunity for targeted therapy in patients with PDAC.